Las características culturales y los contextos de aprendizaje. - Moya Moya, Sara Clemencia (2018)
The aim of this research was to determine the incidence of the cultural characteristics in the educational process of the Educational Unit "Rioblanco Alto" and the School of Basic Education "CBOP. Fausto Espinoza Pinto". This is a mixed method research of exploratory level. First, qualitative data was collected to understand the research problem, then, quantitative data was gathered in order to explain an important cause of the problem. The theoretical background indicates that cultural characteristics is an important factor to take into account in educational institutions with cultural diversity. The qualitative data collected with the different proposed instruments made it possible to demonstrate that cultural characteristics indirectly affect the learning process since there is no intervention by teachers to address the cultural diversity of the students. The process of acculturation is evident because indigenous culture and knowledge are not valued, putting at risk the loss of native customs. Finally, the applied survey indicates that teachers do not have an adequate level of cultural competence, which makes it difficult to guarantee quality intercultural education. Based on these results, it is suggested to develop training to strengthen the teaching profile in cultural competences and strategies and to propose new research that generates didactic proposals from the intercultural approach.